THE INFLUENCE OF PROBIOTIC SUPPLEMENTS ON THE MORPHOLOGICAL AND BIOCHEMICAL PARAMETERS OF QUAIL’S BLOOD IN CRITICAL PERIODS OF DEVELOPMENT - Ohorodnyk Н.; Bosanevych Л.; Tkachuk В.; Pavkovych С.; Dudar І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
The study focuses on the morphological and biochemical characteristics of quail blood during critical developmental phases. The research shows that the Pharaon breed of quails undergo age-related changes that affect leukopoiesis, erythropoiesis, and hematopoiesis. Specifically, it was observed that the number of leukocytes in the blood of quails increases during critical periods of development. In addition, an increase in the number of erythrocytes in the blood of quails was noted, which was associated with the age-related increase in erythropoiesis. The study also found a higher concentration of hemoglobin in the blood of quails in the control group on the 45th day of life, which was related to hormonal changes in the body. In all age periods, the hematocrit value in the blood of quails in the control group was higher. Furthermore, feeding quails with a standard diet supplemented with probiotic additives containing strains of symbiotic microorganisms Lactobacillus acidophilus and Enterococcus faecium had a positive influence on the oxygen transport function of blood during critical developmental phases. The addition of the probiotic supplement resulted in an increase in hemoglobin concentration in the blood of quails on the 35th day (P<0.05) and the 60th day (P<0.01). In comparison to the control group, a decrease (P<0.001) in hematocrit levels in the blood of quails of the experimental group was observed on the 35th day, indicating an increase in blood volume and the ratio of erythrocytes due to the inclusion of the probiotic feed additive in the diet. In all age periods, under the influence of the probiotic supplement, the blood of quails showed a higher content of erythrocytes than in the control. The number of leukocytes decreased in the blood of poultry in the experimental group, which indicated the normalizing effect of the probiotic on leukopoiesis during critical developmental phases.